2014
DOI: 10.1093/nar/gku811
|View full text |Cite
|
Sign up to set email alerts
|

Synonymous codon bias and functional constraint on GC3-related DNA backbone dynamics in the prokaryotic nucleoid

Abstract: While mRNA stability has been demonstrated to control rates of translation, generating both global and local synonymous codon biases in many unicellular organisms, this explanation cannot adequately explain why codon bias strongly tracks neighboring intergene GC content; suggesting that structural dynamics of DNA might also influence codon choice. Because minor groove width is highly governed by 3-base periodicity in GC, the existence of triplet-based codons might imply a functional role for the optimization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 77 publications
3
26
0
Order By: Relevance
“…The alternative synonymous codons do not occur equally; they instead follow a special codon usage pattern, a phenomenon termed codon usage bias [9]. Several factors are known to contribute to codon usage bias, such as mutational bias, translational and transcriptional selection, protein structure, tRNA abundance, RNA stability, GC content, gene expression level, and gene length [10–12].…”
Section: Introductionmentioning
confidence: 99%
“…The alternative synonymous codons do not occur equally; they instead follow a special codon usage pattern, a phenomenon termed codon usage bias [9]. Several factors are known to contribute to codon usage bias, such as mutational bias, translational and transcriptional selection, protein structure, tRNA abundance, RNA stability, GC content, gene expression level, and gene length [10–12].…”
Section: Introductionmentioning
confidence: 99%
“…Then, given the relevance between the synonymous code usage bias and the intrinsic DNA flexibility, we employed the ωGC3 value to estimate the strength of selection pressure which the two groups endured. The ωGC3 value represents the strength of natural selection acting on intrinsic DNA flexibility according to Babbitt's method (Babbitt et al ., ), which was calculated based on the mutational impact ( dTRX obs ) and the simulated neutral impact ( dTRX neutral ) on the intrinsic flexibility of synonymous sites. The box plot showed that the ωGC3 values for the T MGT ≤ 20°C group were higher than those for the T MGT > 20°C group ( P < 0.002) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, intrinsic DNA flexibility was most important to the optimization of local DNA molecular dynamics. From the above, we can conclude that the GC content at synonymous sites (≈GC3) is strongly associated with intrinsic DNA flexibility and optimization of local DNA molecular dynamics (Babbitt et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In both prokaryotic and eukaryotic genes, the synonymous codon usage is non-random [24,25]. It has been postulated that genes in any genome follow a particular codon usage pattern that is similar within the same organism and members of related species [24,26].…”
mentioning
confidence: 99%